Media Pembelajaran PIPAS Interaktif Berbasis Scratch: Perancangan dan Evaluasi pada Siswa Kelas X SMKN 1 Bukittinggi - Rizka Hamidah; Supratman Zakir; Liza Efriyanti; Supriadi Supriadi (Intellect : Indonesian Journal of Learning and Technological Innovation, 2025)
This study was motivated by the conventional and non-interactive learning process in SMKN 1 Bukittinggi, which causes students to become passive, less motivated, and unable to optimally develop practical skills. The limited availability of technology-based learning media equipped with interactive evaluations also hinders timely and meaningful feedback for students. To address these issues, this research developed PIPAS learning media using the Scratch platform as a solution to enhance learning effectiveness and student engagement. This study employed a Research and Development (R&D) method with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) and was conducted with Grade X students at SMKN 1 Bukittinggi. The resulting product is an interactive learning media in the form of a puzzle designed through coding on the Scratch platform. The validity test conducted by three experts yielded an average score of 0.86, consisting of media experts (0.91), language experts (0.75), and subject-matter experts (0.92). The practicality test by teachers achieved a score of 0.93, while the effectiveness test involving students produced a score of 0.85, indicating high effectiveness. Therefore, the Scratch-based learning media developed in this study is declared valid, practical, and effective for PIPAS instruction, as it enhances students’ learning motivation, interactivity, and conceptual understanding, making it a feasible innovative alternative for learning in vocational schools. Abstrak Pembelajaran di SMKN 1 Bukittinggi masih didominasi metode konvensional yang kurang interaktif sehingga siswa cenderung pasif, kurang termotivasi, dan tidak memperoleh kesempatan optimal untuk mengembangkan keterampilan praktis. Minimnya media pembelajaran berbasis teknologi yang menyediakan evaluasi interaktif juga menghambat pemberian umpan balik secara cepat dan tepat. Untuk mengatasi permasalahan tersebut, penelitian ini mengembangkan media pembelajaran PIPAS berbasis platform Scratch sebagai solusi untuk meningkatkan efektivitas pembelajaran dan keterlibatan siswa. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE (Analyze, Design, Develop, Implement, Evaluate), dan dilaksanakan pada siswa kelas X SMKN 1 Bukittinggi. Produk yang dihasilkan berupa media pembelajaran interaktif dalam bentuk puzzle yang dirancang melalui proses pengkodean pada platform Scratch. Hasil uji validitas oleh tiga ahli menunjukkan nilai rata-rata 0,86, terdiri atas ahli media (0,91), ahli kebahasaan (0,75), dan ahli materi (0,92). Uji praktikalitas oleh guru memperoleh nilai 0,93, sedangkan uji efektivitas oleh siswa menghasilkan nilai 0,85 yang menunjukkan efektivitas tinggi. Dengan demikian, media pembelajaran berbasis Scratch yang dikembangkan dinyatakan valid, praktis, dan efektif untuk digunakan dalam pembelajaran PIPAS, karena mampu meningkatkan motivasi belajar, interaktivitas, serta pemahaman konsep siswa sehingga layak dijadikan alternatif inovatif dalam pembelajaran di SMK.